Effect on Gait Speed, Balance, Motor Symptom Rating, and Quality of Life in Those with Stage I Parkinson's Disease Utilizing LSVT BIG®. (26th February 2017) - Millage, Beth; Vesey, Erin; Finkelstein, Marsha; Anheluk, Mattie
Abstract : Individuals with Parkinson's Disease (PD) are often not referred to Physical Therapy (PT) until there are issues with mobility in later Hoehn and Yahr Stages. There have been no studies outlining the benefits of PT intervention in Stage I only. For persons with PD, deficits in motor function increase over time due to destruction of dopamine-producing cells. LSVT BIG, an exercise program for PD, has been shown to be effective in improving mobility. The purpose of this study was to assess participants functional improvement at a level of minimal clinically important difference (MCID) in one of four outcome measures: Gait Speed, Berg Balance Assessment, Functional Gait Assessment, and Unified Parkinson's Disease Rating Scale Motor Section. Case Description. Nine participants with Stage I PD received LSVT BIG 4x/week for 4 weeks followed by bimonthly participation in a community class. Outcome measurement occurred at baseline, after LSVT BIG, and three months after LSVT BIG. Outcomes. Eight of nine participants (88.9%) achieved MCID in at least one of the four measures at both after and 3 months after LSVT BIG training indicating improvement based on our criteria. Participants in Stage I of PD in this study completed LSVT BIG and demonstrated improved function.